Molecular characteristics and zoonotic potential of enteric protists in domestic dogs and cats in Egypt - Elmahallawy, Ehab Kotb; Gareh, Ahmed; Abu-Okail, Akram; Köster, Pamela C.; Dashti, Alejandro; Asseri, Jamal; Gouda, Asmaa Aboelabbas; Mubaraki, Murad A.; Mohamed, Sara Abdel-Aal; Mohamed, Yasser M.; Hassan, Ehssan Ahmed; Elgendy, Mohamed; et al. (Frontiers in Veterinary Science, 2023)
Introduction: Domestic dogs and cats can be a source of human infection by a wide diversity of zoonotic parasites. Genotyping and subtyping tools are useful in assessing the true public health relevance of canine and feline infections by these pathogens. This study investigated the occurrence, genetic diversity, and zoonotic potential of common diarrhoea-causing enteric protist parasites in household dogs and cats in Egypt, a country where this information is particularly scarce. Methods: In this prospective, cross-sectional study a total of 352 individual faecal samples were collected from dogs (n = 218) and cats (n = 134) in three Egyptian governorates (Dakahlia, Gharbeya, and Giza) during July-December 2021. Detection and identification of Cryptosporidium spp., Giardia duodenalis, Enterocytozoon bieneusi, and Blastocystis sp. were carried out by PCR and Sanger sequencing. Basic epidemiological variables (geographical origin, sex, age, and breed) were examined for association with occurrence of infection by protists. Results: The overall prevalence rates of Cryptosporidium spp. and G. duodenalis were 1.8% (95% CI: 0.5–4.6) and 38.5% (95% CI: 32.0–45.3), respectively, in dogs, and 6.0% (95% CI: 2.6–11.4) and 32.1% (95% CI: 24.3–40.7), respectively, in cats. All canine and feline faecal samples analysed tested negative for E. bieneusi and Blastocystis sp. Dogs from Giza governorate and cats from Dakahlia governorate were at higher risk of infection by Cryptosporidium spp. (P = 0.0006) and G. duodenalis (P = 0.00001), respectively. Sequence analyses identified host-adapted Cryptosporidium canis (n = 4, one of them belonging to novel subtype XXe2) and G. duodenalis assemblages C (n = 1) and D (n = 3) in dogs. In cats the zoonotic C. parvum (n = 5) was more prevalent than host-adapted C. felis (n = 1). Household dogs had a limited (but not negligible) role as source of human giardiasis and cryptosporidiosis, but the unexpected high frequency of zoonotic C. parvum in domestic cats might be a public health concern. This is the first molecular-based description of Cryptosporidium spp. infections in cats in the African continent. Molecular epidemiological data provided can assist health authorities and policy makers in designing effective campaigns to minimize the transmission of enteric protists.